UPAYA MENINGKATKAN HASIL BELAJAR PENALARAN UMUM MELALUI MODEL STAD TERHADAP SISWA SAKOLA KEMBARA - Naswa Az Zahra; Natasya Syifa Hamidah; Nazleanne Fachrezia Moslema; Rani Mawarni Panjaitan Panjaitan (JIP: Jurnal Ilmu Pendidikan, 2025)
This study is based on the issue of low motivation and learning outcomes among students at Sakol Kembara in the General Reasoning subtest of the SNBT. One of the main contributing factors is the use of conventional teacher-centered learning models. The author also identified a significant gap in tryout scores among the students. Therefore, an innovative learning model is needed to enhance student motivation, learning outcomes, and collaboration. This research aims to investigate: (1) the improvement in 12th-grade students' learning outcomes in General Reasoning using the STAD learning model, (2) the effectiveness level of the STAD model compared to the conventional model, (3) the comparison of effectiveness between the conventional and STAD methods, and (4) whether the STAD cooperative learning model is more effective than the conventional model in teaching General Reasoning. This research uses a quantitative approach with a quasi-experimental design. Data collection techniques include tests and observation. Data analysis involved normality tests, homogeneity tests, and hypothesis testing (t-test). The results show an increase in post-test scores in both classes, but the experimental class demonstrated a higher gain (0.33) compared to the control class (0.23). However, the t-test and ANOVA results indicate that the difference in learning improvement between the two groups was not statistically significant (p > 0.05). This suggests that while the STAD model has the potential to enhance student understanding, the difference is not yet strong enough to be considered significant.